2017
DOI: 10.29278/azd.371067
|View full text |Cite
|
Sign up to set email alerts
|

Botrytis fabae and Bean common mosaic virus (BCMV) are the most common diseases of Faba bean (Vicia faba L.) in TRNC

Abstract: Surveys were conducted on the fields of faba bean culture in Turkish republic of North Cyprus (TRNC) during 2011-2013 indicated that Botrytis fabae and Bean common mosaic virus (BCMV) are the diseases that cause crop loss at economic level. During the field surveys 117 infected plants that have the symptoms of both diseases were collected from 38 different locations. Symptomatologic, morphologic and classic tests indicated that 96 of the faba bean samples had Chocolate spot disease caused by Botrytis fabae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…BCMV and BCMNV have previously been detected in various regions of Turkey (Açıkgöz, 1984;Güzel and Arlı Sökmen, 2003;Kutluk Yılmaz et al, 2002;Çulal Kılıç et al, 2015;Arlı Sökmen et al, 2016;Çolak Ateş et al, 2017). In this study, the occurrence of BCMNV in the collected seed samples in this region determined and DAS-ELISA data indicated that this virus is widely distributed in the selected seed samples of Lakes region.…”
Section: Conclusion and Recommendationssupporting
confidence: 58%
“…BCMV and BCMNV have previously been detected in various regions of Turkey (Açıkgöz, 1984;Güzel and Arlı Sökmen, 2003;Kutluk Yılmaz et al, 2002;Çulal Kılıç et al, 2015;Arlı Sökmen et al, 2016;Çolak Ateş et al, 2017). In this study, the occurrence of BCMNV in the collected seed samples in this region determined and DAS-ELISA data indicated that this virus is widely distributed in the selected seed samples of Lakes region.…”
Section: Conclusion and Recommendationssupporting
confidence: 58%